A mathematical model for a polarisation based orientation measurement principle in time of arival radio localisation systems - Thielecke, Jörn; Eidloth, Andreas (Mautz, R.: International Conference on Indoor Positioning and Indoor Navigation, IPIN 2010, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.amathe

An Orientation Measurement Principle for Time of Arrival Radio Localisation Systems - Eidloth, Andreas; Patino-Studencki, Lucila; Thielecke, Jörn (European Navigation Conference - Global Navigation Satellite Systems (ENC-GNSS), 2009)

Dynamic multipath mitigation applying unscented Kalman filters in local positioning systems - Nowak, Thorsten; Eidloth, Andreas (Wireless Technology Conference (EuWIT), 2010 European, 2010)
Multipath propagation is still one of the major problems in local positioning systems today. Especially in indoor environments, the received signals are disturbed by blockages and reflections. This can lead to a large bias in the user's time-of-arrival (TOA) value. Thus multipath is the most dominant error source for positioning. In order to improve the positioning performance in multipath environments, recent multipath mitigation algorithms based upon the concept of sequential Bayesian estimation are used. The presented approach tries to overcome the multipath problem by estimating the channel dynamics, using Unscented Kalman Filters (UKF). Simulations on artificial and measured channels show the profit of the proposed estimator model. © 2010 EuMA.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.komele.dynami

Dynamic multipath mitigation applying unscented Kalman filters in local positioning systems - Nowak, Thorsten; Eidloth, Andreas (International Journal of Microwave and Wireless Technologies, 2011)
Multipath propagation is still one of the major problems in local positioning systems today. Especially in indoor environments, the received signals are disturbed by blockages and reflections. This can lead to a large bias in the user's time-of-arrival (TOA) value. Thus multipath is the most dominant error source for positioning. In order to improve the positioning performance in multipath environments, recent multipath mitigation algorithms based upon the concept of sequential Bayesian estimation are used. The presented approach tries to overcome the multipath problem by estimating the channel dynamics, using unscented Kalman filters (UKF). Simulations on artificial and measured channels from indoor as well as outdoor environments show the profit of the proposed estimator model. Furthermore, the quality of channel estimation applying the UKF and the channel sounding capabilities of the estimator are shown. © 2011 Cambridge University Press and the European Microwave Association.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.komele.dynami
Keywords: Antennas and propagation for wireless systems; Wireless systems and signal processing

Modelling of Free-Running Clocks for a Virtually Synchronized Microwave Locating System - Thielecke, Jörn; Patino-Studencki, Lucila; Eidloth, Andreas (Modelling of Free-Running Clocks for a Virtually Synchronized Microwave Locating System, 2009)
For a microwave locating system virtual synchronisation of low-cost free-running transmitter clocks is proposed. The synchronisation strategy is based on modelling the transmitter clocks. A stable stochastic model was designed by analysing the correlation function of the observables in the locating system i.e. time of arrival and carrier phase. Exploiting this model in a Kalman filter, a reference receiver estimates the current clock states and distributes them periodically to the mobile receivers enabling them to predict the transmitter clock deviations between updates. The impact of this synchronization scheme on the position accuracy using both simulated and real data is analysed. ©2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.komele.modell
Keywords: Clocks; Positioning; Synchronisation

Untersuchung der WLAN (IEEE 802.11a-OFDM) Performance im mobilen Betrieb bei hohen Relativgeschwindigkeiten - Eidloth, Andreas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)